Capsizing Reason: Wrath as Shipwreck in 17th-century Spanish Literature - Carrie L. Ruiz (Revista de Estudios Sociales)
This article explores the representation of wrath in relation to the topic of shipwreck in literary texts from 17th-century Spain. As seen in the emblematic genre of the time, as well as in novellas and theatre plays, wrath is represented as the shipwreck of reason. Lack of control and the destruction of the mind as consequences of anger are associated with the capsizing of ships in marine storms. From the Renaissance and well into the late 17th-century, a sound mind is figuratively equivalent to the tranquil voyage in which the ship is in control of the maritime space. By contrast, the reckless and uncontrollable mind is comparable to the ship tossed and destroyed by the tempest, unable to return from the abyss of the ocean depths. As demonstrated in the literary texts of the time, to let the mind be taken over by the passions, particularly wrath and love, was frequently correlated with madness and, thus, with moral decline, as under contemporaneous thought, insanity was connected to ethical degeneration and conversely, sanity with Christian virtues. Moreover, the symbolic implication of the shipwreck motif in Early Modern Spanish literature also reflected the medical notions of the time—namely those related to the bodily humors. Within these sociocultural coordinates, wrath and unrequited love are correlated to choleric and melancholic natures that can lead to madness and social unrest. In sum, the connection of wrath to nautical devastation is an effective means to convey social and political commentary and transmit didactic messages.